Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Kolam Renang Syafira Kecamatan Burneh Kabupaten Bangkalan - Fitrianti Fitrianti; Ruski Ruski; Subandi Widjaya (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study was made to determine the effect of price and service quality on visitor satisfaction at Syafira Swimming Pool, Burneh District, Bangkalan Regency.The independent variables in this study were price and service quality, while the dependent variable in this study was visitor satisfaction.The population in this study were all visitors who visited the Syafira swimming pool.The sample in this study is the entire population. The technique used in sampling is a random sampling technique where all individuals in the population have the opportunity to become members of the sample. Data collection techniques used are questionnaires and documentation. And the analysis technique used is MANOVA (Multivariate Analysis Of Variance). The results of the study show that price has an influence on the visitor satisfaction variable, because the price variable has a positive effect because the price variable shows a sig value of 0.024< 0.05 and tcount>ttable or 2.391>2.051, it can be concluded that H0 is rejected and Ha is accepted. And the quality of service has an effect on the visitor satisfaction variable, because the service quality variable has a positive effect because the service quality variable shows that the sig value is 0.002<0.05 and tcount>ttable or 3.489>2.051, so it can be concluded that HO is rejected and Ha is accepted.